Harsh parenting, physical health, and the protective role of positive parent-adolescent relationships. (May 2016) - Schofield, Thomas J.; Conger, Rand D.; Gonzales, Joseph E.; Merrick, Melissa T.
Abstract: Rationale: Harsh, abusive and rejecting behavior by parents toward their adolescents is associated with increased risk of many developmental problems for youth. Objective: In the present study we address behaviors of co-parents that might help disrupt the hypothesized health risk of harsh parenting. Method: Data come from a community study of 451 early adolescents followed into adulthood. During early adolescence, observers rated both parents separately on harshness towards the adolescent. Adolescents reported on their physical health at multiple assessments from age 12 through age 20, and on parental warmth. Results: Harsh parenting predicted declines in adolescent self-reported physical health and increases in adolescent body mass index (BMI). Although the health risk associated with harshness from one parent was buffered by warmth from the other parent, warmth from the second parent augmented the association between harshness from the first parent and change over time in adolescent BMI. Conclusion: As appropriate, preventive interventions should include a focus on spousal or partner behaviors in their educational or treatment programs. Additional research is needed on the association between self-reported physical health and BMI in adolescence. Highlights: Observed harsh parenting predicts decreases over time in adolescent physical health. Observed harsh parenting predicts increases over time in adolescent body mass index. Warmth from one parent buffers the health risk of harshness from the second parent.